POTENSI PEMBIASAAN SANITASI DAN PELAKSANAAN TRIAS UKS DI LEMBAGA PAUD KECAMATAN LOWOKWARU KOTA MALANG - Shafa, Febbi (Jurnal Penelitian Anak Usia Dini, 2023)
Sanitation is one of the important factors in helping to create optimal growth and development in children, PAUD institutions are one of the key factors in creating and fostering sanitation habits, one of which is through the Triassic UKS program. The purpose of this paper is to determine sanitation habits in early childhood and the implementation of Triassic UKS in PAUD institutions, especially those in the Lowokwaru sub-district of Malang city. The approach used in this research is quantitative approach using survey method. The sampling technique in this study is purposive random sampling technique in PAUD institutions, namely KB/TK/RA and SPS (Similar PAUD Units) in the form of PAUD post. Meanwhile, the data analysis technique used is descriptive percentage analysis technique. The findings of the result show that most PAUD institutions in Lowokwaru sub district have the potential to carry out sanitation and Triassic UKS, but KB/TK/RA institutions are superior in carrying out both of these things compared to SPS (Similar PAUD Units) in the form of PAUD post. Keywords: Sanitation, Triassic UKS, PAUD